PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - ZAHROH, HIKMATUZ (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of institutional ownership on firm value and financial performance as an intervening variable. Research observations were made on manufacturing companies listed on the Indonesia Stock Exchange for three years (2014-2016). The sample of this study was determined by purposive sampling method which was chosen based on the criteria that had been determined so that 120 data were available to be studied. In this study, the hypothesis was tested using a path analysis technique which was carried out through a linear regression analysis test. The results of this study indicate that institutional ownership (KI) affects the value of the company (NP). Institutional ownership (KI) affects financial performance (ROA), financial performance (ROA) affects the value of the company (NP). Financial performance (ROA) is not able to mediate the relationship between institutional ownership (KI) to firm value (NP). Keywords: Institusional Ownership, Firm Value, Financial Performance